O estilo hagiográfico na figura do padre Gabriel Malagrida: o modelo de santidade na segunda metade do século XVIII - Silva, Rodrigo Pires Vilela da (2014)
This dissertation develops on the issue seen as hagiographic literature from the life of Father Gabriel Malagrida which aims to extract an understanding of holiness from the colonial era . Problematizes the subject , with the backdrop of theological reflection , questions such as: What is the cultural context in which the narratives of the life of Malagrida then inserted ? You can establish a hagiographic model of holiness from the investigation of biographies of Malagrida ? What is the relationship that we establish between narrative Matias Rodrigues , Life of Father Gabriel Malagrida and more relevant information about the lives of saints hagiographic work , Legenda Aurea ? The method used is the investigation of literary , biographical and hagiographic literature of life Malagrida and other texts that contribute in understanding the thematic sources. The research aims to contribute to this approach in the valuation of a character of historical importance to Brazil , Jesuit Malagrida . It was found , first, that the current model of holiness has its origins in the medieval conception of Portuguese mother permeates all Brazilian colony . Then proved the hypothesis that an investigation of biographical works Malagrida views from the understanding of hagiographic literature , could provide us sufficient evidence to establish a model of colonial medieval holiness. Finally , we relate this concept to the hagiography contained in Legenda Aurea in order to delineate this paradigm of holiness